2022
DOI: 10.3390/ijerph191710928
|View full text |Cite
|
Sign up to set email alerts
|

MMDCP: Multi-Modal Dental Caries Prediction for Decision Support System Using Deep Learning

Abstract: In recent years, healthcare has gained unprecedented attention from researchers in the field of Human health science and technology. Oral health, a subdomain of healthcare described as being very complex, is threatened by diseases like dental caries, gum disease, oral cancer, etc. The critical point is to propose an identification mechanism to prevent the population from being affected by these diseases. The large amount of online data allows scholars to perform tremendous research on health conditions, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Ngnamsie Njimbouom et al developed a decision support system based on machine learning algorithms to assist in treatment planning for dental caries [ 8 ]. A similar study of the use of AI was also reported on the regarding the detection of fluoride concentration in drinking water in Turkey, and the results showed that the use of AI was cheaper, faster, and more feasible than the use of many chemical analysis techniques available in the laboratory [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngnamsie Njimbouom et al developed a decision support system based on machine learning algorithms to assist in treatment planning for dental caries [ 8 ]. A similar study of the use of AI was also reported on the regarding the detection of fluoride concentration in drinking water in Turkey, and the results showed that the use of AI was cheaper, faster, and more feasible than the use of many chemical analysis techniques available in the laboratory [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond caries detection, Ngnamsie Njimbouom et al developed a decision support system based on machine learning algorithms to assist with treatment planning for dental caries [ 8 ]. The study revealed that the system significantly improved treatment consistency among dental professionals, highlighting the potential benefits of AI integration into dental practice.…”
Section: Introductionmentioning
confidence: 99%
“…Several crucial procedures are involved in the initial data preprocessing to guarantee the consistency and usefulness of the secondary dataset [28]. This includes scaling the dental radiography pictures to a joint resolution so that the deep learning model can process them consistently.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Throughout the years, with the ever-increasing amounts of data, computational models (machine learning-based solutions) have proven effective in addressing a diverse range of practical issues in public healthcare [ 13 , 14 , 15 ], bioinformatics [ 16 ], natural language processing (NLP) [ 17 ], and many others.…”
Section: Introductionmentioning
confidence: 99%